2016
DOI: 10.4103/1463-1741.189241
|View full text |Cite
|
Sign up to set email alerts
|

Occupational noise and ischemic heart disease: A systematic review

Abstract: Noise exposure might be a risk factor for ischemic heart disease (IHD). Unlike residential exposure, however, evidence for occupational noise is limited. Given that high-quality quantitative synthesis of existing data is highly warranted for occupational safety and policy, we aimed at conducting a systematic review and meta-analysis of the risks of IHD morbidity and mortality because of occupational noise exposure. We carried out a systematic search in MEDLINE, EMBASE, and on the Internet since April 2, 2015, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
(88 reference statements)
2
23
0
Order By: Relevance
“…Previous studies show an association between occupational noise and cardiovascular diseases and studies showing association with living in cold climate and cardiovascular diseases (Analitis et al 2008;Dzhambov and Dimitrova 2016;Eriksson et al 2018;Gasparrini et al 2015;Skogstad et al 2016;Song et al 2017;Theorell et al 2016). However, to our knowledge this is the first study that shows an interaction between 7 1911-1920 8004 4.1 1921-1930 14,818 7.6 1931-1940 25,017 12.9 1941-1950 46,543 23.9 1951-1960 40,364 20.8 1961-1970 51,901 26.7 1971-1980 occupational noise, cold temperatures and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies show an association between occupational noise and cardiovascular diseases and studies showing association with living in cold climate and cardiovascular diseases (Analitis et al 2008;Dzhambov and Dimitrova 2016;Eriksson et al 2018;Gasparrini et al 2015;Skogstad et al 2016;Song et al 2017;Theorell et al 2016). However, to our knowledge this is the first study that shows an interaction between 7 1911-1920 8004 4.1 1921-1930 14,818 7.6 1931-1940 25,017 12.9 1941-1950 46,543 23.9 1951-1960 40,364 20.8 1961-1970 51,901 26.7 1971-1980 occupational noise, cold temperatures and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies indicate that occupational noise has non-auditory effects on the cardiovascular health such as increased risks of hypertension, coronary heart disease, and stroke (Dzhambov and Dimitrova 2016;Skogstad et al 2016;Theorell et al 2016). Several studies have found that living in cold climate or cooling of the body increases mortality in cardiovascular disease (Analitis et al 2008;Gasparrini et al 2015;Song et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the unresolvable differences in the metrics across the selected studies, a quality assessment and quantitative meta-analysis under the quality-effects model were not possible [ 34 ]. Therefore, a qualitative approach to data synthesis was adopted to answer the review question.…”
Section: Methodsmentioning
confidence: 99%
“…It used objective measure of road traffi c noise and adjusted for most of the relevant covariates. 4,5 Like some previous studies 6,14 ours has limitations. Its cross-sectional design means that we could not confi rm that the exposure preceded the outcome.…”
Section: Strengths and Limitationsmentioning
confidence: 82%
“…Heretofore, studies have been discordant due to differences in design and exposure/outcome defi nition. 5 Gan et al 6 reported OR=2.04 (95% CI: 1.16, 3.58) among people exposed to loud noise for 1.6 -18.8 years, Virkkunen et al 7 found HR = 1.27 (95% CI:1.13,1.44) for those exposed to > 80 dB during an 18-year follow-up, while Jovanovic et al 8 did not fi nd elevated odds for exposure to > 80 dB, and neither did Thériault et al 9 Overall, although there was some evidence to suggest higher risk of IHD morbidity, it was limited. 5 In Bulgaria, this topic is a pressing issue given that both IHD and noise exposure are highly prevalent.…”
mentioning
confidence: 99%